Maharah al-Kalam al-‘Arabiy wa Mukawwanatuha wa Ahdafuha wa Taqwimuha - Khoirurrijal Khoirurrijal; Erlina Erlina (Jurnal Internasional Pendidikan Bahasa Arab, 2019)
The speaking ability is the important skill of Arabic teaching. The ability of Arabic speech is the skill to perform the voice and expressing something meaningful in the mind of the speaker. This research aims to find out the component, the purpose, and the evaluation of Arabic speech. This is library research. This research found that the components of Arabic speech are pronunciation, vocabulary and grammar. The purpose of Arabic speech skills is the students are able to speak fluently and correctly and performing vocabularies that they learn and including the meanings that can send information to others in the social situation. Evaluation of Arabic speech skills is insist of the integrity of the vocabulary with pronunciation on the condition of the right situation, the validity of using vocabulary that acceptable in the tongue of the Arabs, and the validity of using Arabic stylistics that Arabian used.